A compositive control method of low‐voltage ride through for PMSG‐based wind turbine generator system. Issue 1 (2nd October 2017) - Xing, Pengxiang; Fu, Lijun; Wang, Gang; Wang, Yi; Zhang, Yan
Abstract : Converting the surplus power into rotor kinetic energy by changing the control functions of machine side converter (MSC) and grid side converter (GSC) is considered to be an efficient way for permanent magnet synchronous generator (PMSG)‐based wind turbine generator system (WTGS) to accomplish low‐voltage ride through (LVRT) without additional hardware components. However, because of the time delay of grid fault detection and the control system inertia, the dc‐link capacitor may still be subjected to overvoltage in the early tens of milliseconds after a grid fault happens. This study proposes a compositive control method of LVRT for PMSG‐based WTGS, in which the surplus power during LVRT is converted into rotor kinetic energy by controlling the electrical power of the PMSG according to the grid‐connected power of the GSC, and a crowbar circuit is reserved to consume the surplus power before MSC reacts to the grid fault. The proposed method does not change the control functions of MSC and GSC, and the related control parameters resetting can be avoid. Besides, it can also provide reactive power support to assist the grid voltage recovery. Simulations and experiments proved the proposed method to be feasible and effective.